Rancang Bangun Lettekost.id Sebagai Sistem Infromasi Kost Berbasis Website Di Kota Makassar - Ahmad Salman; Muhammad Jamil; Valentino Aris (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The development of digital technology is driving digital transformation in various sectors, including the provision of housing search services such as boarding houses. This research aims to design and implement a website-based boarding house search information system, Lettekost.id. The method used is Research and Development (R&D) with the Design Thinking development model (emphasize, define, ideate, prototype, test). Validation results by three validators indicate that the tested features function well. Evaluation using the System Usability Scale (SUS) resulted in a score of 83, indicating a good level of usability.